Intercommunications of indexes of general physical training of fencer on swords different qualifying groups. - Hohla A.I. (Pedagogìka, Psihologìâ ta Mediko-bìologìčnì Problemi Fìzičnogo Vihovannâ ì Sportu, 2012)
Purpose of work - to find out the presence of cross-correlation intercommunications between the indexes of general physical preparedness and dependence of their structure from the level of sporting qualification of sportsmen. 66 sportsmen took part in research. From them 35 are sportsmen of I-II of digits, 31 are highly skilled sportsmen. Sportsmen executed 14 tests which characterize the level of general physical preparedness. For the sportsmen of spark-gaps found out 15 reliable cross-correlation intercommunications of direct (10) and reverse (5) character. For skilled sportsmen - 18: (9) direct and (9) reverse character. For the sportsmen of spark-gaps the most of reliable intercommunications is set between spray force (6) and explosive force of feet (5). At skilled - between figure (7) and spray (6) force and other indexes. The presence of direct cross-correlation intercommunications between physical qualities testifies about expedience of their complex development in one training employment. Reverse - about the necessity of the differentiated development of such physical qualities.